Assessing marine species vulnerability to projected warming on the Scotian Shelf, Canada. (26th February 2015) - Stortini, Christine H.; Shackell, Nancy L.; Tyedmers, Peter; Beazley, Karen
Abstract: Resource managers need climate adaptation tools. We build on a popular tool, the climate change vulnerability assessment (CCVA), to identify vulnerable marine species. Only warming was considered, as warming is expected to have earlier impacts in the offshore than other climate drivers, and projections of other climate drivers are not well developed. For this reason, we coin our generalized, semi-quantitative method the "Vulnerability to Projected Warming Assessment" (VPWA) as opposed to using the broader term, CCVA. We refine the typical "exposure" component to be a function of gain/loss of thermal habitat at multiple life stages. We also build on the traditional logic approach of CCVAs. We produce scores for each species, and use a null distribution through Monte Carlo simulations to identify the most vulnerable species. We evaluate the vulnerability of 33 fish and invertebrate species, on the scale of the Scotian Shelf, Canada, to two warming scenarios, mild and severe, based on regional trends and projections. At smaller spatial scales, we evaluate populations of a subset of these species. Populations in the southwest portion of the domain are found to be more vulnerable than those in the northeast. Overall, our results indicate that 45% of populations may be vulnerable under a severe (+3°C) warming scenario, including currently endangered, threatened, and commercial populations (e.g. southwestern Atlantic cod, Smooth skate, Snow crab), while only one species has a relatively high vulnerability score under the mild (+0.7°C) scenario (Moustache sculpin). Populations triaged by relative vulnerability to regional warming should help managers prioritize resources and identify knowledge gaps. For this reason, and for its biological and ecological underpinnings, our method has broad relevance within the marine science and management field. As more information become available, our VPWA can be used as a stepping-stone in the continued development of CCVA methods.